2013
DOI: 10.4103/2152-7806.121644
|View full text |Cite
|
Sign up to set email alerts
|

Management of trigeminal neuralgia in sclerosteosis

Abstract: Background:Sclerosteosis is a rare bone disorder characterized by a progressive craniotubular hyperostosis. The diagnosis of sclerosteosis is based on characteristic clinical and radiographic features and a family history consistent with autosomal recessive inheritance. The skull overgrowth may lead to lethal elevation of intracranial pressure, distortion of the face, and entrapment of cranial nerves, resulting in recurrent facial palsy or secondary trigeminal neuralgia.Cases Description:The authors reported c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Trigeminal neuralgia is relatively a rare presentation of sclerosteosis that was present in this case. It is usually refractory to medical treatment [11], but in our case, the pain responded well to corticosteroid and pregabalin. Another fatal complication is sudden death, which is caused by the impaction of the medulla oblongata in the foramen magnum due to the progressive rise of intracranial pressure (ICP) by bony overgrowth [3].…”
Section: Discussionmentioning
confidence: 56%
“…Trigeminal neuralgia is relatively a rare presentation of sclerosteosis that was present in this case. It is usually refractory to medical treatment [11], but in our case, the pain responded well to corticosteroid and pregabalin. Another fatal complication is sudden death, which is caused by the impaction of the medulla oblongata in the foramen magnum due to the progressive rise of intracranial pressure (ICP) by bony overgrowth [3].…”
Section: Discussionmentioning
confidence: 56%
“…Patients with Sclerosteosis, van Buchem Disease, or HBM associated with LRP5 mutations often suffer from neuropathies and other sequelae due to nerve impingements caused by increased bone mass [11][12][13][14][15]. We show here that when treated with Wnt secretion inhibitors, genetic mouse models that replicate human HBM have bone mass reduced to more normal levels, therefore establishing this approach as a potential strategy for treating HBM patients to reduce neuropathy.…”
Section: Discussionmentioning
confidence: 65%
“…Sclerosteosis patients have even more severe symptoms that can reduce lifespan. These include cranial vascular and neural foraminal narrowing and reduced intracranial volume, frequent seventh nerve palsy, progressive optic and cranial neuropathies, mixed hearing loss, brainstem compression, intracranial hypertension with increased elastance, and sudden, premature death [12][13][14][15]. Thus, it is critical to identify approaches that can reduce the pain and morbidity seen in these patients to improve their quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with megadolichobasilar artery, the results have been shown to be better, with a 93.1% rate of remaining pain-free without medication after 6 months to a rate of 75.7% chance after 2 years, when the results remained stable for up to 13 years after treatment 57 . In sclerosteosis, Andrade et al 6 suggested radiosurgery as a treatment option despite the lack of published data.…”
Section: Painmentioning
confidence: 99%